(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
Artificial intelligence has become an increasingly significant pedagogical tool in higher education, particularly in disciplines where language, interpretation, translation, textual analysis, academic writing, and intercultural communication are central. Philology students require individualized academic support because their learning needs differ in vocabulary development, grammar accuracy, reading comprehension, writing competence, translation practice, pronunciation, discourse awareness, and literary interpretation. Although numerous studies have examined the general role of artificial intelligence in education, less attention has been paid to its potential for supporting personalized learning specifically among philology students. This article investigates how artificial intelligence can function as an essential tool for personalized learning in philological education. The study applies a qualitative literature-based analytical method and synthesizes recent research on artificial intelligence in higher education, personalized learning, AI-assisted language learning, learner autonomy, feedback, and academic integrity. The findings indicate that AI can support philology students through adaptive explanations, individualized feedback, vocabulary and grammar support, writing assistance, translation comparison, pronunciation practice, self-assessment, and flexible learning pathways. However, the article also emphasizes that AI should not replace the teacher’s pedagogical, ethical, and emotional role. Challenges such as overdependence, plagiarism, inaccurate information, algorithmic bias, weak critical thinking, and data privacy concerns must be addressed through clear institutional policies and AI literacy. The article concludes that artificial intelligence can become an effective pedagogical assistant for philology students when it is used critically, ethically, and under teacher guidance.